Long-term effect of manuring-fertilization on nutrients availability and yield under rice (Oryza sativa)-lentil (Lens culinaris) system - SINGH, PRIYA; BISWAS, SUNANDA; GHOSHAL, NANDITA; DE, NIRMAL; SINGH, DIVYADARSHAN (The Indian Journal of Agricultural Sciences, 2023)
Soil health degradation is a major threat in agricultural sustainability specially under rainfed agriculture. The purpose of this study was to assess the impact of long-term fertilization and manuring on soil organic carbon, nutrient status, uptake and yield trends under a rainfed rice (Oryza sativa L.)-lentil (Lens culinaris L.) cropping system situated at Agriculture Research Farm of Banaras Hindu University, Varanasi, Uttar Pradesh. Soil samples were collected in 2019 and 2021 after harvesting of rainy (kharif) season rice from 34 years old long-term experiment with rice-lentil cropping system of dry sub-humid region of India and analysed for various pools of SOC, nutrients availability, uptake and yield attributes. Results showed that 50% NPK+FYM treatment significantly influenced soil organic carbon pools and improved macronutrients (Nitrogen, Phosphorus, Potassium), microbial biomass carbon and dehydrogenase activity in soil as compared to the control. In addition, the integrated application of farmyard manure and inorganic fertilizers significantly enhanced the nutrient uptake, productivity of rice and lentil, and maintained the nutrient balance in the soil. Therefore, the balanced use of inorganic fertilizer along with organic manure may be recommended for maintaining soil health and crop productivity under subtropical India.